The impact of guidance counselling on gender segregation: Major choice and persistence in higher education. An experimental study - Erdmann, Melinda; Schneider, Juliana; Pietrzyk, Irena; Jacob, Marita; Helbig, Marcel (Frontiers in Sociology, 2023)
Gender segregation in higher education is considered one of the main drivers of persistent economic gender inequality. Yet, though there has been considerable research identifying and describing the underlying mechanisms that cause gendered educational choices in higher education, little is known about how gender segregation in higher education could be changed. Accordingly, this article aims to determine the potential of educational interventions during high school to foster gender desegregation in higher education. We focused on two different processes that contribute to gender segregation in majors among higher education graduates: first, the selection into specific majors and, second, the selection out of specific majors. We investigated whether an intensive counselling programme leads to more gender-atypical choices among high-school graduates and examined whether intensive counselling supports several indicators of students’ persistence in gender-atypical majors. Based on data from an experimental study of a counselling programme for German high-school students (N = 625), we estimated the programme’s effect with linear probability models and intention-to-treat analysis. Our results show that high-school graduates are more likely to choose a gender-atypical major if they have received intensive counselling. This applies more to men than to women. In addition, the programme improved some persistence indicators for students in gender-atypical majors. Although we found a significant programme effect only for perceived person–major fit and student satisfaction, the coefficients of all aspects of students’ persistence show a trend indicating that the programme was beneficial for students in gender-atypical majors. As experimental studies can also be affected by various types of bias, we performed several robustness checks. All analyses indicated stable results. In conclusion, we suggest that intensive counselling programmes have the potential to reduce gender segregation in higher education. More students were motivated to choose a gender-atypical major, and different aspects of student persistence were supported by the programme for students in gender-atypical majors.